Pengembangan Media Pembelajaran 3 Dimensi “Rolling Ball Game” Pada Mata Pelajaran Akidah Akhlak di Madrasah Tsanawiyah - Aulia, Dika; Ramadhani, Nurul (South Sulawesi Education Development, 2024)
This article discusses the development of the 3-dimensional learning medium